Democratic Systems Increase Outgroup Tolerance Through Opinion Sharing and Voting: An International Perspective - Hu, Fei; Lee, I-Ching (Frontiers in Psychology, 2018)
Democracy may contribute to friendly attitudes and positive attitudes toward outgroups (i.e., outgroup tolerance) because members of democratic societies learn to exercise their rights (i.e., cast a vote) and, in the process, listen to different opinions. Study 1 was a survey study with representative samples from 33 countries (N = 45, 070, 53.6% female) and it showed a positive association between the levels of democracy and outgroup tolerance after controlling for gender, age and the rate of immigrants influx from 2010 to 2013. Study 1 demonstrated that members in countries with higher political participation and civil liberty showed greater tolerance toward immigrants. In Study 2, we conducted an experimental study in Taiwan (N = 93, 67.7% female) to further examine two potential mediators (opinion sharing and voting) of the effect of democratic system on tolerance toward outgroups (i.e., attitudes toward mental patients) after controlling for gender and age. We found that when individuals were allowed to share opinions and vote, they had the highest positive other-oriented emotions toward mental patients, which in turn led to greater tolerance toward outgroups compared to those who were not allowed to share opinions or vote. In general, these results demonstrated that the democratic system plays a critical role in increasing outgroup tolerance. Limitations of the two studies and implications regarding opinion sharing, voting, democratic systems, and effects on outgroup tolerance are discussed.